1996
DOI: 10.1116/1.588655
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated phase shift mask materials for 248 and 193 nm lithography

Abstract: Articles you may be interested in X-ray mask fabrication technology for 0.1 μm very large scale integrated circuits A multilayer inorganic antireflective system for use in 248 nm deep ultraviolet lithography In order to push resolution toward diffraction limits for 248 and 193 nm lithography, it is likely that some combination of optical enhancement may be needed. The attenuated phase shift mask approach may prove to be one of the less complex techniques available. Four materials are presented which may meet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…This thickness, d, was then used to calculate transmission as a function of n and k using Equation 9. [11,12] An extinction coefficient was found for a particular transmission and index of refraction, and lines were superimposed on the contour plot for 4% and 15% transmission. Shown in Figure 10 is the contour plot of degree of polarization vs. n and k with transmission lines overlaid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This thickness, d, was then used to calculate transmission as a function of n and k using Equation 9. [11,12] An extinction coefficient was found for a particular transmission and index of refraction, and lines were superimposed on the contour plot for 4% and 15% transmission. Shown in Figure 10 is the contour plot of degree of polarization vs. n and k with transmission lines overlaid.…”
Section: Resultsmentioning
confidence: 99%
“…The index of refraction was varied from 0.5 to 3.0 (increments of 0.1) and the extinction coefficient from 0.0 to 1.0 (increments of 0.1). The thickness necessary to obtain a ¡ -phase shift was calculated for a particular n and k value by first using Equation 7 to calculate the interfacial phase jump at the substrate-mask material interface ( ¢ ¤ £ 12 ), the mask material-air interface ( ¢ ¤ £ 23 ), and the substrate-air interface ( ¢ ¤ £ 13 ), and using these values in Equation 8 to solve for d. [11] A plot of APSM film thickness vs. n and k is shown in Figure 9. This thickness, d, was then used to calculate transmission as a function of n and k using Equation 9.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a bi-layer attenuated phase shift mask (AttPSM) made up of an absorber layer, such as tantalum (Ta), and a transparent layer, such as silicon-oxi-nitride (SiON), can provide independent tuning of the transmission and phase [1]. Experimental work has shown that such a TaSiON mask provides an exposure latitude (EL) improvement over standard masks (6% molybdenum-oxide silicon-oxide (MoSi) AttPSM and chrome-oxi-nitride (Cr) binary films) [2].…”
Section: Introductionmentioning
confidence: 99%
“…[3,41. Silicon nitride films prepared for DUV APSM's not only have good durability for moisture and alkali ions, and high mechanical strength. but also possess suitable optical constants, and good etching selectivity against a fused silica substrate without the need of a stopping layer [5,6]. However, the absorption coefficient of a silicon nitride film is too large to be as an APSM layer in \TUV regime.…”
Section: Introductionmentioning
confidence: 99%